The Hard Power Dan Soft Power Penyelesaian Konflik Aceh (Tahun 1976 – 2005) - Nurul Fajri; Novita Sari (FISIP UWP, 2023)
The Free Aceh Movement (GAM), declared by Hasan Tiro in 1976, was a form of disappointment caused by the central government's centralism. Not only that, Aceh also supported Indonesia's struggle against the Dutch to maintain independence. Aceh also contributed a considerable amount, even referred to as the capital region of the Republic of Indonesia by Soekarno. The purpose of this research is to find out the state of Aceh before the rebellion of the Free Aceh Movement, the factors that caused the rebellion of the Free Aceh Movement, the rebellion process of the Free Aceh Movement in 1976-2005, and the efforts of the Indonesian government in realising peace in Aceh. The method used is descriptive qualitative method where data is collected through literature study, interviews and documentation. The results showed that economic factors, culture and disappointment in Aceh were the causes of the rebellion. In the next development, the rebellion claimed many victims, especially civilians. In the process towards peace, state leaders have their own ways to achieve peace with the Free Aceh Movement. The peace agreement between the Government of Indonesia and the Free Aceh Movement occurred through negotiations in Helsinki, known as the Helsinki MoU.